News About Persons (Academy of Management Journal, 1971)
The article announced that Gundar J. King was promoted to the position of Vice President of Programs of the Western Association of Collegiate Schools of Business and that Jay W. Lorsch was appointed to the position of Professor of Organizational Behavior at Harvard University Graduate School of Business Administration.